Combination Effects of Cymbopogon sp. Essential Oil on Selected Bacteria - Nur Aishah Abdul Wahab; Hairul Shahril Muhamad; Salina Mat Radzi; Maryam Mohamed Rehan; Hanina Mohd Noor; Nabilah Ahmad Alhadi (Universiti Sains Islam Malaysia, 2024)
Combination effects between Cymbopogon flexuosus and Cymbopogon nardus essential oils were studied to determine whether the combination could emerge as better and more powerful antimicrobial agents against six selected bacteria includes Bacillus subtilis,Escherichia coli,Salmonella typhimurium,Serratia marcescens,Staphylococcus aureus,andStaphylococcus epidermidis. This combination study exhibited 40.67% additive, 28.67% antagonistic, 16.00% indifferent and 14.66% synergistic effects. C. flexuosus and C. nardus essential oils in combination showed a high inhibitory activity against S. aureus with 16% synergistic, 64% additive and 20% indifferent effects.